Treatment of Traumatic Umbilical Hernia with Peritonitis due to Intestinal Perforation in a Three-Month Old Calf. Issue 1 (2016) - Zafar, Muhammad Arif; Yousaf, Arfan; Murtaz-ul-Hasan, Murtaz-ul-Hasan; Kiayani, Faisal Ayub; Islam, Matee ul; Iqbal, Muhammad Farooq
No abstract available